Winter moon [large type] - Paine, Lauran (Circle V western., 2018)
"U.S. Marshal John Galloway has been tracking the four members of the Streeter gang for some time from Texas to the Pacific Northwest to Montana and into northern Wyoming heading towards a showdown in the town of Brigham"--